Technology News - No. 539 - Identifying the Benefits of Engineering Noise Controls Through a Business Case (The National Institute for Occupational Safety and Health (NIOSH), 2009)
To develop a business case that promotes adoption of noise controls by reducing barriers to industry acceptance and enhancing drivers that foster their implementation. Background Over 75% of the U.S. mining workforce is exposed to hazardous noise, putting them at risk of noise-induced hearing loss (NIHL). Consequently, coal miners suffer high rates of hearing impairment that increase to 70%-90% by retirement age. To address the noise problem for coal miners, researchers from the National Institute for Occupational Safety and Health (NIOSH) first determined that the continuous mining machine (CMM) ranked first among machines associated with reported coal noise overexposures. Further studies found that most CMM noise is generated by three component systems on the machine: dust collection, cutting, and conveying. Of these systems, the on-board chain conveyor was found to be a dominant noise source. Noise generated by the conveying system was addressed through the development of a urethane-coated flight bar chain. The coated chain, shown in Figure 1, has demonstrated an 8-hour time-weighted average (TWA) reduction of operator exposure by 3 dB(A). It has since been accepted by the Mine Safety and Health Administration (MSHA) as a "technologically achievable" noise control for CMM operators who are exposed to noise that exceeds the MSHA permissible exposure level. Having demonstrated the noise reduction performance of the coated chain, NIOSH has assembled information into a business case that can be used by operations considering adopting the chain at their worksite.